Sami'na Wa Atha'na Concepts of Education in Humanistic Learning Theory Perspectives - Amir Bandar Abdul Majid; Suyadi (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2021)
The purpose of this research is to find humanistic values in pesantren education that traditionally still use sami'na wa atha'na habits. This research is a type of qualitative research that uses a descriptive approach. The form of data presentation is taken from pesantrens in Yogyakarta, namely Pondok Al-Munawwir Kerapyak, Pondok Ulul Albab Balirejo, and Pondok Wahid Hasyim Nologaten. The results showed that humanistic education can be applied in pesantrens and not Contrary to the Qu'an and Hadith . Humanistic education in its development in pesantren is divided into three, namely 1) Humanistic based on purpose; 2) Humanistic based process; 3) Humanistic based on pesantren curriculum.